Penerapan Teknik Collaborative Writing (CW) terhadap Peningkatan Emotional Intelligence (EI) - Rahmani, Eka Fajar (Universitas Tanjungpura, 2024)
This study investigates the implementation of collaborative writing technique in developing emotional intelligence of students. The participants are students of Sekolah Tinggi Bahasa Inggris Pontianak who took Essay Writing and Literary Criticism class. This study employs qualitative methodology with a questionnaire to collect the intended data referring to the five domains of emotional intelligence suggested by Goleman (1996) and Serrat (2017), namely self-awareness, self-regulation, self-motivation, social awareness, and social skills. The results of the data analysis indicated that collaborative writing technique is indeed helpful in developing the students